Frequency of Urgent or Emergent Vitreoretinal Surgical Procedures in the United States During the COVID-19 Pandemic - Breazzano, Mark P; Nair, Archana A; Arevalo, J Fernando; Barakat, Mark R; Berrocal, Audina M; Chang, Jonathan S; Chen, Andrew; Eliott, Dean; Garg, Sunir J; Ghadiali, Quraish; Gong, Dan; Grewal, Dilraj S; et al. (JAMA ophthalmology, 2021)
The American Academy of Ophthalmology (AAO) indicated that urgent or emergent vitreoretinal surgical procedures should continue during the coronavirus disease 2019 (COVID-19) pandemic. Although decreases in the frequency of critical procedures have been reported outside the field of ophthalmology, analyses are limited by volume, geography, and time. To evaluate whether the frequency of ophthalmic surgical procedures deemed urgent or emergent by the AAO changed across the United States during the COVID-19 pandemic. Vitreoretinal practices from 17 institutions throughout the US participated in this multicenter cross-sectional study. The frequency of 11 billed vitreoretinal Current Procedural Terminology (CPT) codes across respective weeks was obtained from each practice between January 1, 2019, and May 31, 2020. Data were clustered into intravitreal injections (code 67028), lasers and cryotherapy (codes 67141, 67145, and 67228), retinal detachment (RD) repairs (codes 67107, 67108, 67110, and 67113), and other vitrectomies (codes 67036, 67039, and 67040). Institutions were categorized by region (Northeast, Midwest, South, and West Coast), practice setting (academic [tax-exempt] or private [non-tax-exempt]), and date of respective statewide stay-at-home orders. Nationwide changes in the frequency of billing for urgent or emergent vitreoretinal surgical procedures during the COVID-19 pandemic. A total of 526 536 CPT codes were ascertained: 483 313 injections, 19 257 lasers or cryotherapy, 14 949 RD repairs, and 9017 other vitrectomies. Relative to 2019, a weekly institutional decrease in injections was observed from March 30 to May 2, 2020, with a maximal 38.6% decrease (from a mean [SD] of 437.8 [436.3] to 273.8 [269.0] injections) from April 6 to 12, 2020 (95% CI, -259 to -69 injections; P = .002). A weekly decrease was also identified that spanned a longer interval, at least until study conclusion (March 16 to May 31, 2020), for lasers and cryotherapy, with a maximal 79.6% decrease (from a mean [SD] of 6.6 [7.7] to 1.5 [2.0] procedures) from April 6 to 12, 2020 (95% CI, -6.8 to -3.3 procedures; P < .001), for RD repairs, with a maximal 59.4% decrease (from a mean [SD] of 3.5 [4.0] to 1.6 [2.2] repairs) from April 13 to 19, 2020 (95% CI, -2.7 to -1.4 repairs; P < .001), and for other vitrectomies, with a maximal 84.3% decrease (from a mean [SD] of 3.0 [3.1] to 0.4 [0.8] other vitrectomies) from April 6 to 12, 2020 (95% CI, -3.3 to -1.8 other vitrectomies; P < .001). No differences were identified by region, setting, or state-level stay-at-home order adjustment. Although the AAO endorsed the continued performance of urgent or emergent vitreoretinal surgical procedures, the frequency of such procedures throughout the country experienced a substantial decrease that may persist after the COVID-19 pandemic's initial exponential growth phase. This decrease appears independent of region, setting, and state-level stay-at-home orders. It is unknown to what extent vitreoretinal intervention would have decreased without AAO recommendations, and how the decrease is associated with outcomes. Although safety is paramount during the COVID-19 pandemic, practices should consider prioritizing availability for managing high-acuity conditions until underlying reasons for the reduction are fully appreciated.